2021
DOI: 10.1111/1758-2229.12925
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the interaction of carbon, nitrogen, and temperature on the biosynthesis of Aureobasidium pullulans antifungal volatiles

Abstract: The combined biochemical impact of carbon, nitrogen and temperature on the biosynthesis of the antifungal volatile organic compounds (VOCs): ethanol, 2-methyl-1-propanol, 3-methyl-1-butanol and 2phenylethanol produced by Aureobasidium pullulans A1 and A3 was investigated using a Box-Behnken experimental design and response surface methodology (RSM). Normalized peak areas derived from solid phase micro extraction-gas chromatography-mass spectrometry (SPME-GC-MS) analysis, indicated that initial carbon content h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Carbon metabolism plays a decisive role in biological growth and amino acid biosynthesis [41,42] . Iwmer [43] found that during induced and targeted metabolic modi cations in plants, cellular equilibrium is disrupted, carbon metabolism is inhibited, leading to excess carbon sources, and cells synthesize amino acids in large quantities or initiate other non-related metabolic pathways, resulting in metabolic ine ciencies Yalage et al [44] investigated the combined effect of carbon concentration and incubation temperature on the biosynthesis of VOCs was investigated using a Box-Behnken experimental design. In this study, the carbon metabolism pathway was signi cantly enriched in the cyan module based on KEGG enrichment analysis.…”
Section: Role Of Carbon Metabolic Pathways Submergence Stressmentioning
confidence: 99%
“…Carbon metabolism plays a decisive role in biological growth and amino acid biosynthesis [41,42] . Iwmer [43] found that during induced and targeted metabolic modi cations in plants, cellular equilibrium is disrupted, carbon metabolism is inhibited, leading to excess carbon sources, and cells synthesize amino acids in large quantities or initiate other non-related metabolic pathways, resulting in metabolic ine ciencies Yalage et al [44] investigated the combined effect of carbon concentration and incubation temperature on the biosynthesis of VOCs was investigated using a Box-Behnken experimental design. In this study, the carbon metabolism pathway was signi cantly enriched in the cyan module based on KEGG enrichment analysis.…”
Section: Role Of Carbon Metabolic Pathways Submergence Stressmentioning
confidence: 99%
“…Although fungi can obtain amino acids from a range of sources, including exogenous amino acids in their environment, degradation of endogenous proteins, and de novo biosynthesis, the specific mechanisms utilized by fungi to acquire amino acids and the role of amino acid metabolism in nutrient acquisition are intricate and not yet fully understood. In general, amino acid metabolism in fungi is intimately linked to other metabolic pathways, such as nitrogen metabolism and carbon metabolism [36,37]. The mechanisms used by a given fungus to obtain amino acids depend on its ecological niche, nutrient availability, and metabolic capabilities.…”
Section: Introductionmentioning
confidence: 99%